Building form regulation visualisation in Japan: automatic building volume legality verification via procedural modelling. (3rd April 2019) - Chen, Hangyu; Shen, Zhenjiang
Building Standard Law (BSL) in Japan serves to establish minimum standards relating to the site, structure, facility, and function of buildings. Building form regulation (BFR) in BSL controls the building volume according to the zone restrictions contained within a district plan. In Japan, one of the building permission (BP) procedures involves determining whether building volume is legal or not according to BFR. This paper proposes a 3D BFR visualisation which allows for efficient legality verification under BP. We establish shape parameters to transform BFR into a 3D shape reflective of certain land conditions which affect the attributes in CityEngine. We then utilise the 3D BFR shape visualisation to validate the building volume legality automatically in python script. We hope that the results presented here improve the efficiency of the BP procedure. And regulations may be combined into the city data. It is meaningful for the future development of smart cities.